Application of adaptive robust control for electro-hydraulic motion loading system. (February 2018) - Chengwen, Wang; Zongxia, Jiao; Long, Quan; Hongjun, Meng
This paper investigates the problem of the high-performance motion loading control of an electro-hydraulic load simulator (EHLS). To begin with, the non-linear motion loading model of the EHLS was developed, by which the external disturbances caused by actuator active motion and the uncertainties arising from the EHLS were comprehensively considered. To address these uncertainties and disturbances, the adaptive robust torque control algorithm was developed with the motion loading model. In contrast to the available control methods concerning the EHLS, the developed method has two advantages. First, instead of performing the fixed coefficients-based linear feed-forward compensation using the actuator velocity, adaptive non-linear feed-forward compensation is achieved through the back-stepping design procedure. Second, the uncertainties and disturbances including system parametric uncertainties, un-modelled friction dynamics and unknown external disturbance are addressed comprehensively. Besides illustrating the theoretical proof, the effectiveness of the proposed method is verified through comparative experiments.